2019
DOI: 10.1016/j.chemosphere.2019.06.155
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and depuration kinetics of dicofol metabolite 4,4′-dichlorobenzophenone, in the edible Asiatic clam Meretrix meretrix

Abstract: Uptake and depuration kinetics of 4,4′-dichlorobenzophenone (main metabolite of dicofol) in the edible clam Meretrix meretrix were evaluated through a mesocosm experiment. M. meretrix was exposed to different dicofol concentrations (environmental concentration, D1 = 50 ng/L; supra-environmental concentration, D2 = 500 ng/L) for 15 days, followed by the same depuration period. To accomplish this goal, an analytical method was successfully optimized for 4,4′-DCBP using QuEChERS as extraction method with a range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Since its residues in the environment are persistent, [4][5][6] they can easily cause serious environmental pollution and even pose a threat to organisms in the environment including humans. [7][8][9][10] In recent years, many studies have shown that exposure to DIC in the environment or its residues in foods has severe toxic effects on various mammals and humans, especially on aquatic organisms. [11][12][13][14] To reduce hazards involving food safety and human health, the use of DIC on crops has been strictly limited.…”
Section: Introductionmentioning
confidence: 99%
“…Since its residues in the environment are persistent, [4][5][6] they can easily cause serious environmental pollution and even pose a threat to organisms in the environment including humans. [7][8][9][10] In recent years, many studies have shown that exposure to DIC in the environment or its residues in foods has severe toxic effects on various mammals and humans, especially on aquatic organisms. [11][12][13][14] To reduce hazards involving food safety and human health, the use of DIC on crops has been strictly limited.…”
Section: Introductionmentioning
confidence: 99%
“…2,11 Due to a long history of using these chemicals, they accumulate in agricultural fields. 12 Many techniques have been developed to analyze OCPs in various matrices such as soil, food, blood, human fat, liver, kidney, etc. [13][14][15] In general, analytes in a real sample are measured after a pretreatment to reduce matrix effects.…”
Section: Introductionmentioning
confidence: 99%